Professional health regulation in the public interest international perspectives - Chamberlain, John Martyn 1972-; Saks, Mike 1952-; Dent, Mike 1944- (Sociology of health professions, 2018)
Bringing together leading academics worldwide, this collection compares and critically examines the ways in which different countries are regulating healthcare in general, and health professions in particular, in the interest of users and the wider public